Decomposing door-to-needle time: insights into workflow delays and quality improvement in acute stroke care - Lianyan Wei; Hongfei Li; Zhuangzhuang Jiang; Dongjuan Xu; Xiaolan Wu (Frontiers in Neurology, 2025)
BackgroundTimely administration of intravenous recombinant tissue plasminogen activator (rtPA) significantly improves outcomes in acute ischemic stroke (AIS). However, substantial variability in door-to-needle (DTN) time persists in real-world settings. This study aimed to deconstruct DTN time into distinct workflow intervals to identify key determinants of delay and inform targeted quality improvement.MethodsThis retrospective study included 322 consecutive AIS patients treated with intravenous rtPA at Dongyang People’s Hospital between May 2023 and April 2025. DTN time was divided into four intervals: door-to-order time (ODT), order-to-imaging completion time (OCT), imaging completion-to-consent time (ICT), and consent-to-needle time (CNT). Real-time data were collected through beacon-based tracking and a time-tracking application. Linear regression, correlation, and subgroup analyses were used to explore factors associated with each interval and overall DTN time.ResultsAmong all intervals, ICT showed the strongest correlation with DTN time (r = 0.845, p < 0.01), followed by CNT and OCT. Imaging-guided thrombolysis significantly prolonged DTN time by 32.29 min (p < 0.0001), mainly through delays in ICT and OCT. Thrombolysis led by senior physicians was associated with a 7.61-min reduction in DTN time (p < 0.0001), driven by shorter ICT and CNT. MRI-negative strokes significantly prolonged DTN time by 6.28 min (p < 0.05), primarily due to a delay in ODT. Subgroup analysis revealed that junior physicians were more likely to cause delays during off-hours. Imaging-guided thrombolysis, such as CTP-guided and MRI-guided approaches, significantly prolonged DTN time due to extended OCT and ICT intervals (p < 0.001). Semiannual trends showed a gradual improvement in DTN performance until T3 (May–October 2024), followed by a plateau in T4 (November 2024–April 2025), possibly due to increased use of imaging-guided thrombolysis and more complex referrals.ConclusionPhysician seniority, thrombolysis strategy, and MRI-negative status significantly influence DTN time. Segmenting DTN time enables precise identification of key delays across different workflow stages and may enhance the efficiency of acute stroke care.